Managing the external financing constraints of social enterprises: A systematic review of a diversified research landscape - Lena Schätzlein; Deike Schlütter; Rüdiger Hahn (International Journal of Management Reviews, 2022)
Social enterprises, located between non-profit organisations and for-profit firms, often struggle to acquire external funding. An increasing amount of research on the external financing of social enterprises stems from a fragmented body of the literature anchored in a variety of subject areas (e.g. entrepreneurship, public sector management, general management and strategy). We systematically review 204 academic articles published between 1998 and 2021 to bridge the knowledge gaps in these subject areas by: (1) mapping the field of the external financing of social enterprises at the individual, organisational and institutional levels; (2) synthesising the findings to develop an overarching framework; and (3) discussing theoretically sound future research avenues. We find that research at the individual level focuses primarily on investors' perspective of the ideal characteristics of a social entrepreneur. Research at the organisational level often addresses the dual logics of social enterprises and their impact on the successful financing of these businesses and the role of investor–investee collaboration. Research at the institutional level can be clustered into cultural, economic, political and legal factors. Overall, we stress the need for research that adopts an overarching view by considering all three levels of analysis simultaneously and using organisational and economic theories.
Keywords: 650